Perancangan Sistem Informasi Presensi Siswa PKL Pada CV Uniti Kebumen - Rapiyanta, Paulus Tofan; Batul, Zahroil; Iswahyuni, Dwi (LPPM Universitas Bina Sarana Informatika, 2024)
CV Uniti is a company located in Kebumen, Central Java, Indonesia. This company has established collaborative relationships with Vocational High Schools in Kebumen to carry out the activities of internship program/ Field Work Practices (PKL). The attendance system of internship program students in CV Uniti is still manual. This manual method is less effective because students have to take turns in filling attendance sheet, it may cause problems such as data loss or data damage, and students can manipulate their attendance. Therefore, the objective of this study was to design a web-based attendance information system to make it easier for internship program students to fill attendance and facilitate the supervisors in monitoring the student attendance and giving assessment for internship program students. The research methods included the observation of the running system in CV Uniti, interviews to the students and supervisors as well as the literature studies as the supporting data. The software development method used is prototyping consisting of listening to customers, building and repairing prototypes, and testing prototypes. The software development method used is a prototype, which consists of engaging customers, building, and improving the prototype and testing. The results of the research indicate that the internship program students attendance information system is capable of conducting the internship program activities and providing feedback. In addition to this, a computerized system can help internship program supervisor to monitor and managing students remotely.